Cardiac vagus nerve denervation by pulmonary vein isolation was effective for swallowing‐induced atrial tachycardia. Issue 1 (16th July 2021) - Yamaguchi, Yoshiaki; Sakamoto, Tamotsu; Nakatani, Yosuke; Mizumaki, Koichi
Abstract: Swallowing‐induced atrial tachycardia (SIAT) is a relatively rare arrhythmia. A 56‐year‐old woman was admitted to treat atrial tachycardia that occurs by not only eating and drinking but also yawning. Both the right and left upper pulmonary veins were suspected as the earliest activation site of the tachycardia and the abnormal activation of ectopies themselves were suppressed after pulmonary vein isolation (PVI). In a 24‐hour Holter electrocardiogram, the HF component of the analysis of heart rate variability was suppressed both at 1 day and at 2 years after ablation. In this case, cardiac vagal nerve denervation by PVI was effective for SIAT.